The Need for the Evaluation of Sport-Specific Skills in Paralympic Goalball with a 3-D Kinematic Analysis: Research Note - Esatbeyoglu, Ferhat; Kirkaya, Izzet; Senaysoy, Safa; Bicici-Ulusahin, Seda (Sagamore Publishing Llc, 2024)
Goalball is one of the Paralympic sport disciplines designed for athletes with visual impairments (VI), and athletes wear eyeshades while they perform the sport for a fair competition. The game is played with a ball with bells inside allowing its movement to be heard by the players and therefore sport -specific attack and defense foundations needs to be developed for this Paralympic sport discipline. Taking the VI into account, movement phases of attack and defense techniques may be improved by the coach with proper training programs and with this, athletic ability of the athlete with VI may be enhanced. This is especially significant for novice goalball athletes as mastering fundamental skills properly may lead to better performance on the court while minimizing the risk of injury. In contrast, there is a scarce literature on examining the kinematic analysis of Paralympic goalball sport. Limited studies carried out 2-D video observational analysis for goalball -throwing technique and in fact goalball-throwing technique is three dimensional. Moreover, studies conducted kinematic analysis only for throwing technique. For these reasons, 3-D kinematic analysis of throwing and defense techniques is essential. In addition, development of throwing and defense techniques with precise training methods requires taking into account of kinetic chain of body segments, functional movement must be considered and evaluated completely. From this point of view, functional training methods that can contribute defense performance can be recommended as there is no study evaluating the functional performance of goalball athletes. This also can contribute to development of goalball specific test protocols to evaluate foundational goalball skills and novel training approaches can be applied in order to develop physiological and motor skills of goalball sport.
Keywords: Goalball; offensive skill; defensive skill; visual impairment; functionality; motion analysis; athletic training